Negotiating the “Spatial Turn” in European Cross-Border Governance: Notes on a Research Agenda - Kramsch, Olivier Thomas (Geopolítica(s). Revista de estudios sobre espacio y poder, 2012)
Acknowledging the slippery nature of the term “governance”, the paper begins by canvassing a “first-wave” of academic reflection on the governance of European cross-border regions, emergent in the early to mid-1990s amid a EU-phoric plethora of institutional innovations designed to create “laboratories of European integration” within and across the internal borders formerly dividing European member states. The paper then excavates the limitations of this theoretical sediment, arguing that by drawing on literatures rooted in public administration and political science, the properly spatial dimension of cross-border governance has been muted, if not rendered invisible. The paper seeks to address this shortcoming by focusing on insights offered up by the “spatial turn” in geography and the wider social sciences as they relate to the increasingly visible problematic of transboundary governance evident at this time. Through this conceptual frame the author argues for a normative as well as theoretical specificity to cross-border regional spatiality, one which foregrounds the fact that, rather than merely epiphenomenal or derivative to state space, European cross-border regions (or, euregios) today are themselves important sites where the very meaning of “the political” is being negotiated, contested, resisted and transformed. The paper suggests that a way forward in the analysis of governance in Europe’s cross-border regions will demand breaking beyond several key assumptions of the mainstream border studies literature, notably the by now mantra-like insistence of borders as involving primarily identitarian distinctions between “Us and Them”, and, concomitantly with this outlook, an understanding of internal European borders and cross-border regions as idiographically unique appendages to state territoriality. In contradistinction to these hegemonic assumptions, a postcolonial, “contrapuntal” research agenda is posed, one which seeks to actively counter the logic of reducing cross-border “difference” to the “Same” by way of a renewed comparative perspectivalism.
Keywords: governance; cross-border regions; spatial turn; Same/difference; decolonization; frontier